1996
DOI: 10.1016/0737-6782(96)00025-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating R&D and marketing: A review and analysis of the literature

Abstract: The trend toward leaner, flatter organizations enhances the need for communication and cooperation between the marketing and the R&D functions. This paper reviews evidence of the need for integrative communication and cooperation, research on the barriers to integration, and extant models to study integration. We summarize this research and these models with a causal map to organize research on integration at the new-product project-level. Within this framework we review research on the methods that managers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
511
1
12

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(537 citation statements)
references
References 14 publications
13
511
1
12
Order By: Relevance
“…'' In this article, we address the question of whether marketing should be cross-functional and, more specifically, whether those firms that have greater influence of functional groups outside of marketing in the firm's marketing activities achieve better performance in the market. While many researchers have argued for positive performance implications of cross-functional interaction in the decision process such as improved coordination and integration, improved learning, spanning of organizational boundaries, reduced cycle times, and enhanced new product development (Denison et al, 1996;Griffin and Hauser, 1996), there are also possible dysfunctional effects of such a cross-functional approach. Specifically, decisions could be slowed down since more people with different interests are involved in the decision process (Cespedes, 1995) and even though different functional groups interact, there might be detrimental disharmony (Souder, 1988) and conflict (Weinrauch and Anderson, 1982) between them.…”
mentioning
confidence: 99%
“…'' In this article, we address the question of whether marketing should be cross-functional and, more specifically, whether those firms that have greater influence of functional groups outside of marketing in the firm's marketing activities achieve better performance in the market. While many researchers have argued for positive performance implications of cross-functional interaction in the decision process such as improved coordination and integration, improved learning, spanning of organizational boundaries, reduced cycle times, and enhanced new product development (Denison et al, 1996;Griffin and Hauser, 1996), there are also possible dysfunctional effects of such a cross-functional approach. Specifically, decisions could be slowed down since more people with different interests are involved in the decision process (Cespedes, 1995) and even though different functional groups interact, there might be detrimental disharmony (Souder, 1988) and conflict (Weinrauch and Anderson, 1982) between them.…”
mentioning
confidence: 99%
“…Research on multi-disciplinary projects has shown that this type of cooperation is very often characterized by a state of severe disharmony (Gupta & Wilemon, 1988;Souder, 1988). Numerous variables have been identified that may be responsible for these interface problems (Griffin & Hauser, 1996). Several of the most important factors are related to personal barriers.…”
Section: Interdisciplinary Cooperation In New Venture Creationmentioning
confidence: 99%
“…After all, multi-disciplinary new venture teams are more likely to make adequate decisions in the founding process (Roberts, 1991;Roure & Maidique, 1986). Although it is important, interdisciplinary cooperation is often characterized by severe disharmony, both in new venture teams and in new product development teams (Griffin & Hauser, 1996;Gupta & Wilemon, 1988;Souder, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various teamwork and cross-functional cooperative relationships, the one between R&D and marketing is considered as one of the most important and challenging to manage (Rodríguez, Pérez, & Gutiérrez, 2007;Rodríguez, Pérez, & Gutiérrez, 2007a;Becker & Lillemark, 2006;Sherman, Berkowitz, & Souder, 2005;Shaw et al, 2004;Atuahene-Gima & Evangelista, 2000;Song et al, 1996). Empirical studies have found that, despite a complex and often problematic relationship, successful R&D-marketing collaboration can help a firm better understand customer needs and preferences (Griffin & Hauser, 1996); reduce new product development (NPD) uncertainties (Becker & Lillemark, 2006;Song et al, 1996); improve the performance of a new product in terms of quality, cost and time-to-market (Shaw et al, 2004;Song & Parry, 1997;Swink & Song, 2007); and improve the success rate of new products (Massey & Kyriazis, 2007).…”
Section: Randd-marketing Cooperationmentioning
confidence: 99%